(untitled) (Socio-economic relations in the digital society, 2019)
Proposed to application of the method of expert assessments to assess the attractiveness of investment projects.are considered Th e theoretical aspects of the method of expert assessments and been demonstrated the use of these methods on a specifi c task. In the case of the limited information or authenticity the methodof expert assessments gives good results and further ways of improving them. On the particular task are shown reasons for using the concordance coeffi cient. Note, however, that scientifi cally grounded results can be achieved only when is thought out folded a group of experts and implemented the fundamental principlesof the expert survey.